Pengaruh Inovasi Terbuka Terhadap Kinerja Inovasi Pada UKM di Indonesia - Muhammad Nabil Alfarobi; Arif Hartono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of open innovation on product innovation and the innovation performance of SMEs in Indonesia. The source of data used in this study is secondary data obtained from Indonesia innovation survey (IIS) 2014 that covers 2011-2013 period. The analytical technique used in this research is descriptive analysis and SEM analysis using the AMOS statistic software. The results show that: (1) open innovation (external search breadth) had a positive effect on product innovation, by contrast open innovation (external search depth) had no significant effect on product innovation; (2) Internal R&D had a positive effect on product innovation, in contrast external R&D had no significant effect on product innovation; (3) collaborative practices has not had a positive effect on product innovation; (4) product innovation has a significant effect on innovation performance.